"It's a life-altering experience": Examining the role of care environments in the experience of breast cancer care - Devotta, Kimberly A. (My University, 2012)
Ontario’s Regional Cancer Programs provide an organized system of adjuvant treatment and follow-up care in its 13 Regional Cancer Centres. For breast cancer patients in particular, these centres become a part of daily activities, as appointments over five years of cancer care result in patients repeatedly accessing these centres at varying frequencies over their treatment periods. The experience of seeking out and receiving care has grown to incorporate cancer care services that exist on a variety of spatial scales, in both formal and informal environments (e.g. support groups, workshops). This study focuses on the role of geography in health behaviors and care experiences of breast cancer patients. Individual interviews were conducted with patients (n=23) attending the Juravinski Cancer Centre in Hamilton, Ontario about their care experiences in their community, and the location and organization of the centre. Rosenstock’s (1966) health belief model and Bandura’s (1986) social cognitive theory informed the analysis of patient satisfaction and produced attitudes that impact the likelihood of health action. Results demonstrated that patients were generally satisfied with their interactions with health care providers and the design and location of the centre. Parking and perceived disconnect between the centre and community health care providers (e.g. family doctors) were identified as being sources of patient dissatisfaction. Patients made sense of their care experience through ‘routinization’ – fixed times and predictable intervals – of travel and appointment schedules. Satisfaction with accessibility to health care providers when at home (e.g. call-in services) appeared to impact at-home adherence to medication and suggested lifestyle changes. Uptake of community support services depended on patient perceptions of need, suitability and proximity, but went largely unused. Patients’ understanding of their care experiences highlight the need to give greater consideration to geography and the physical care environment in the future planning of breast cancer care services.
Keywords: breast cancer; care environments; health belief model; regionalized care; Juravinski Cancer Centre; Human Geography; Human Geography